Criminal Responsibility Scale: Development and Validation of a Psychometric Tool Structured in Clinical Vignettes for Criminal Responsibility Assessments in Brazil - Meyer, Leonardo Fernandez; Leal, Cláudia Cristina Studart; Omena, Alexandre de Almeida Souza; Mecler, Katia; Valença, Alexandre Martins (Frontiers in Psychiatry, 2020)
Criminal responsibility assessment is implemented by psychologists or psychiatrists assessing legal capacities as defined by law, which varies among countries or regional legislations. There are two psychometric tools (i.e., checklists) validated for criminal responsibility assessment: the Roger Criminal Responsibility Scale, and the rating scale of criminal responsibility for mentally disordered offenders. Despite the existence of psychometric tools structured in clinical vignettes for evaluating legal capacities, none serve the purpose of assessing criminal responsibility. This study aims to validate a novel psychometric tool, structured in vignettes for assessment of criminal responsibility called the “Criminal Responsibility Scale.” We applied the psychometric tool to 88 defendants referred for criminal responsibility assessment in a forensic medical institute in the city of Rio de Janeiro, Brazil, from December 2017 to December 2018. Afterward, the final score was compared with the expert’s conclusion in each case. The criminal responsibility scale and sub-scales were evaluated using confirmatory factor analysis. The two-factor solution proved satisfactory and met the needs for practical application of the Criminal Responsibility Scale (Kaiser–Meyer–Oklin= 0.82; p< .001). Moreover, the inter-rater reliability was satisfactory (k= .667-1.0), and the resulting cutoff point was 30.50 (±2), with the Youden index of 0.509. Hence, the Criminal Responsibility Scale is an effective psychometric tool for assessments of criminal responsibility that may encourage future research in assessments of legal capacity with clinical vignette-based psychometric instruments.